Jerusalem ; v. 1 the topography, economics and history from the earliest times to A.D. 70. - Smith, George Adam, 1856-1942 (London, UK Hodder and Stoughton, 1907)
Contents : v. 1 : Introduction, the topography, the economics and politics. Includes biobliographical references, maps and indexes. Note map inside back dust jacket flap.
Keywords: Bible -- History of contemporary events; Jerusalem in the Bible